Antara Larangan dan Kebolehan: Analisis Kritis Hadis-hadis tentang Musik dalam Islam - Siregar, Hakkul Yakin (Yayasan Albahriah Jamiah Indonesia, 2025)
The debate on the law of music in Islam has been going on for a long time and has involved many scholars with diverse views. Some hadiths seem to strictly prohibit music, while others provide room for permissibility, depending on the context and purpose of its use. The background of this study is the need to comprehensively and critically understand the hadiths related to music and how scholars interpret these texts within the framework of Islamic law. This study aims to critically examine the hadiths about music and evaluate the differences in interpretation among classical and contemporary scholars. The method used is a qualitative study based on descriptive-critical analysis of relevant hadiths, supplemented by a search for hadith narrations and the opinions of scholars from various schools of thought. The results of the study indicate that hadiths about music need to be studied from the aspects of sanad, matan, and socio-historical context. Some hadiths that are considered to prohibit music are considered weak by some scholars, while hadiths that are permissive are strengthened by the principle of maqashid al-Shari’ah and ethical considerations. In conclusion, the law of music cannot be generalized as haram or halal absolutely, but rather needs to be seen from the purpose, content, and impact of the music on spirituality and morality. This study provides space for a more moderate and contextual approach to understanding music from an Islamic perspective.